PENGARUH IMPLEMENTASI SISTEM IRIGASI BIG GUN SPRINKLER DAN BAHAN ORGANIK TERHADAP KELENGASAN TANAH DAN PRODUKSI JAGUNG DI LAHAN KERING - Donny Nugroho K; S Sudarto; H Haryono (Jurnal Tanah dan Sumberdaya Lahan, 2018)
Dry land in Indonesia has high potential for agricultural development because of its area, but its utilization is still not optimal. Low water availability is a major issue on dry land. The availability of water is affected by the topography and physical properties in dry land in the holding or to save water. Easy removable irrigation systems such as the Big Gun Sprinkler can meet water demands, while adding organic material can prolong its availability. The purpose of this study  was to analyze the effect of the use of Big Gun Sprinkler irrigation system and organic material against moisture of soil and maize yield. Experimental design used in this research was a Split Splot design with two factors, the first factor was dose the water with three levels consisting of A1 ((100% dose of water), A2 (85% dose of water), A3 (70% dose of water), and the second factor was a dose of organic matter with three levels consisting of B1 (3 t ha-1), B2 (4 t ha-1), B3 (5 t ha-1), and the combination of these factors that consisted of three replicates. The results of this study showed that with irrigation systems water distribution was not uniform because of the influence of the distance from the centre and the wind. Combination of doses of water and organic matter did not give significant influence over all  parameters. However, each treatment produced different values on each parameter.